Isotopic components and source analysis of inorganic nitrogen in coastal aerosols of the Yellow Sea - Zhang, Ke; Liu, Sumei; Wu, Nian; Xu, Wenqi (Frontiers in Marine Science, 2022)
The coastal atmospheric environment is one of the most complex environments on earth. It is shaped by terrestrial, marine, and atmospheric processes and acts as an external nutrient source for coastal waters. At present, there are few observations of inorganic nitrogen isotopes of China coastal aerosols, let alone the Yellow Sea. In this study, a weekly collection of total suspended particulate aerosols was conducted on the Qianliyan Island in 2018 for the measurements of inorganic nitrogen species (NO3− and NH4+) and their isotopic ratios (δ15N-NO3−, δ18O-NO3−, and δ15N-NH4+). At the Qianliyan Island, the average NO3− and NH4+ concentrations were 2.49 ± 2.12 and 3.33 ± 2.68 μg·m−3, respectively; the average δ15N-NO3−, δ18O-NO3−, and δ15N-NH4+ were 2.4‰ ± 5.7‰, 78.7‰ ± 8.0‰, and −2.6‰ ± 6.3‰, respectively. The major nitrate formation pathways were •OH oxidation and N2O5 hydrolysis paths, and the dominant sources of inorganic nitrogen aerosols were coal combustion (29% ± 7%), marine (19% ± 15%), and fertilizer (16% ± 13%). Aerosol δ15N-NO3− and δ18O-NO3− were obviously higher in winter and lower in summer; conversely, aerosol δ15N-NH4+ was slightly higher in summer and slightly lower in winter. The difference in nitrogen sources was considered to be the best explanation for the aerosol δ15N-NO3− and δ15N-NH4+ differences between summer and winter, of which coal combustion contributed the most. The seasonal difference in nitrate formation paths was considered to be the best explanation for the difference of Qianliyan aerosol nitrate δ18O-NO3− between summer and winter. Aerosol inorganic nitrogen deposition flux was estimated to be 3.4 nmol N·m−2·s−1, which induced less than 1% to marine primary production, and aerosol inorganic nitrogen deposition, compared with N2 fixation, contributed some 80% of δ15N-NO3− depression of the summer Yellow Sea thermocline.